EXPLORING STUDENTS’ RESPONSES (COGNITIVE, AFFECTIVE AND CONATIVE) IN LEARNING READING NARRATIVE TEXT USING QUIZIZZ APPLICATION AS MOBILE ASSISTED LANGUAGE LEARNING (MALL) - Rahmi Tri Lestari; Kusrin; Sumarta (PROJECT (Professional Journal of English Education), 2024)
This study aims to determine students' responses in learning narrative text using the Quizizz application as Mobile Assisted Language Learning (MALL). According to Steven M Chaffe theory, the three categories of responses are; cognitive, affective and conative responses. This study used a qualitative and case study design to conduct this research. The researcher conducts observations, reflective journals, and semi-structured interviews to collect the data. The data analysis used in the research is adopted from Braun & Clarke (2022). The study showed the three categories of student responses (cognitive, affective, and conative) after learning narrative text using the Quizizz application. This study highlights the students’ responses that appeared in this application. In the cognitive aspect, some students understand generic structures, understand language features, understand social functions, identify specific information in stories in learning narrative texts using the Quizizz application. In the affective aspects, some students felt interested, excited, and liked learning narrative text using the Quizizz application. In the conative aspect, some students participate, actively discuss, enthusiasm, and concentrate on learning narrative texts using the Quizizz application. The implication is an increased understanding of student responses in learning narrative text using the Quizizz application in reading classes.